Folklore and mythological basis of the crime in the story "The Fairytale about the snowball tree reedpipe" by Oksana Zabuzhko (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
This article is examined the story by Oksana Zabuzhko “Fairy-tale about a viburnum pan-pipe”, foucusing on folk-lore mythological subsoil base of crime, the attention is applies on the new reading by the authoress of biblical legend about Cain and Avel accomplished by the senior sister, and also folk tale about a viburnum pan-pipe.
Keywords: biblical legend; pan-pipe